2019
DOI: 10.1177/0022034519878412
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Minimally Invasive Orthodontic Tooth Movement Acceleration: A Systematic Review and Meta-analysis

Abstract: Doctors and patients attempt to accelerate orthodontic tooth movement with a minimally invasive surgery approach. The purpose of this systematic review was to evaluate the evidence of accelerated tooth movement in minimally invasive surgery and the adverse effects from it. A systematic search of the literature was performed in the electronic databases of PubMed, CENTRAL (Cochrane Central Register of Controlled Trials), Embase, Scopus, Web of Science, Science Direct, and Medline and was complemented by a manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 50 publications
2
36
0
2
Order By: Relevance
“…However, the 1-month gain of time during treatment does not justify such a procedure even if it is minimally invasive. This was in agreement with Liu et al, 23 who found only low-quality evidence to support that flapless corticotomy could accelerate tooth movement.…”
Section: Discussionsupporting
confidence: 92%
“…However, the 1-month gain of time during treatment does not justify such a procedure even if it is minimally invasive. This was in agreement with Liu et al, 23 who found only low-quality evidence to support that flapless corticotomy could accelerate tooth movement.…”
Section: Discussionsupporting
confidence: 92%
“…These findings demonstrate the effectiveness of the piezocision procedure in accelerating the canine retraction rate with a statistically significant difference. Similar results regarding accelerating tooth movement were made in other studies [12,16,17,36,[45][46][47] but differed in the effect size. Interestingly, Fu et al [17] reported similar results in their meta-analysis, but they included five different surgical interventions, one of them was in combination with laser and pooled heterogeneous methodological and clinical studies in the same meta-analysis.…”
Section: Summary Of Evidencesupporting
confidence: 82%
“…The present meta-analysis has more strength in terms of studies included than other studies [12,[17][18][19], as much related primary research has emerged in the last two years. Also, these studies were not registered in PROSPERO.…”
Section: Plos Onementioning
confidence: 96%
See 2 more Smart Citations